História de vida e constituição dos sujeitos: os alunos em situação de deficiência e a área de Ciências Naturais, Exatas e Tecnológicas - Santos, Daniellle Rita dos (Universidade Federal de São Carlos, 2020)
Entering public higher education is, for many, the fulfillment of a dream, in addition to the right that the social struggles so often achieved in the Law conquered. In the case of students in situations of disabilities, this entry is consolidated through social movements and becomes a historical flag in the fight for rights, which until then was quite absent in the scenario of public higher education in Brazil. In this process, new questions about treatment are mobilized, both in the access and permanence of students at the university, as well as in the career options and training trajectories of these students. Thinking about inclusive practices involves, involving, even if in a limited perspective, understanding who are these students in situations of disabilities that enter in a higher education. Bearing in mind that courses linked to the area of Natural, Exact and Technological Sciences are part of a hegemonic area, which has little space for dialogue with a difference, in this research, from the visibility of life histories of students in situations of disabilities , sought - to understand possible intricacies, contexts and factors related to the life histories of young university students, when booking vacancies for People with Disabilities (PwD), who opted for a career in the area of Natural, Exact or Technological Sciences. The study was guided by theoretical discussions related to inclusion in higher education, based on the sociology of disability from the perspective of Michael Foucault and research on entering and staying in the university environment. As the qualitative research methodology, episodic interviews were carried out, and the sequence sought to analyze the way of comprehensive-interpretative analysis of life trajectories and the dialogue with the theoretical references of the analysis. The thematic axes of analysis emerged from childhood, adolescence, a family relationship, a schooling trajectory, a choice by the university and the future plans in their narratives. The study made it possible to embark within the narratives and to look at the formation of disciplinary processes and devices that remain in different conditions, as well as rules and processes that do not depend on the people in situations of disabilities.
Life history and constitution of subjects: students in situation of disabilities and the area of Natural, Exact and Technological Sciences
Keywords: Histórias de vida; Situação de deficiência; Ciências naturais, exatas e tecnológicas; Life histories; Situations of disabilities; Natural, Exact and Technological Sciences; CIENCIAS EXATAS E DA TERRA; CIENCIAS HUMANAS::SOCIOLOGIA; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO